Medical Management of Rheumatic Heart Disease: A Systematic Review of the Evidence. Issue 4 (July 2018) - Russell, E. Anne; Walsh, Warren F.; Costello, Ben; McLellan, Alex J. A.; Brown, Alex; Reid, Christopher M.; Tran, Lavinia; Maguire, Graeme P.
Abstract : Rheumatic heart disease (RHD) is an important cause of heart disease globally. Its management can encompass medical and procedural (catheter and surgical) interventions. Literature pertaining to the medical management of RHD from PubMed 1990–2016 and via selected article reference lists was reviewed. Areas included symptom management, left ventricular dysfunction, rate control in mitral stenosis, atrial fibrillation, anticoagulation, infective endocarditis prophylaxis, and management in pregnancy. Diuretics, angiotensin blockade and beta-blockers for left ventricular dysfunction, and beta-blockers and If inhibitors for rate control in mitral stenosis reduced symptoms and improved left ventricular function, but did not alter disease progression. Rhythm control for atrial fibrillation was preferred, and where this was not possible, rate control with beta-blockers was recommended. Anticoagulation was indicated where there was a history of cardioembolism, atrial fibrillation, spontaneous left atrial contrast, and mechanical prosthetic valves. While warfarin remained the agent of choice for mechanical valve implantation, non-vitamin K antagonist oral anticoagulants may have a role in RHD-related AF, particularly with valvular regurgitation. Evidence for anticoagulation after bioprosthetic valve implantation or mitral valve repair was limited. RHD patients are at increased risk of endocarditis, but the evidence supporting antibiotic prophylaxis before procedures that may induce bacteremia is limited and recommendations vary. The management of RHD in pregnancy presents particular challenges, especially regarding decompensation of previously stable disease, the choice of anticoagulation, and the safety of medications in both pregnancy and breast feeding.